REPRESENTASI IDEOLOGI PATRIARKI DAN PENGARUHNYA TERHADAP TOKOH PEREMPUAN DALAM NOVEL CANTING KARYA ARSWENDO ATMOWILOTO - Handra, Arici; Nurizzati, Nurizzati (Universitas Negeri Padang, 2019)
This research aimed to analyze about the representation of patriarchal ideology and its impact on female characters in the novel Canting by Arswendo Atmowiloto. In addition, the presence of this study can be known forms of patriarchal ideology and its impact on female characters in the novel. This study used qualitative research with descriptive method. The findings in this study are the forms of patriarchal ideology, consists of two forms: (1) private patriarchy is as housewife and a wife (2) public patriarchy that work and activities outside the home. The impact on female characters consisting of (1) violence is psychological violence (2) intimidation is fear of a wife towards her husband (3) of marginalization which restrict the movement of a woman, and (4) the subordination of that workload borne by women.Keywords: patriarchal ideology, Canting novel, violence